A One-Pot Synthesis of Aurones from Substituted Acetophenones and Benzaldehydes: A Concise Synthesis of Aureusidin - Zhao, Xiaolong; Liu, Jie; Xie, Zhixiang; Li, Ying (Synthesis, 2012)
A one-pot synthesis of aurones from substituted acetophenone and benzaldehyde has been developed on the basis of an improved Algar–Flynn–Oyamada reaction. By using this method, several aurones were prepared in three steps from commercial starting materials. The usefulness of this one-pot strategy was confirmed by a synthesis of aureusidin, an inhibitor of iodothyronine deiodinase, in 41% overall yield. In comparison with a two-step synthesis of this product from the same substrates, the one-pot strategy was more effective, giving a higher yield and requiring fewer and simpler operations.
Keywords: heterocycles; natural products; total synthesis; cyclizations; furans; bicyclic compounds